Maximizing Learning Ability: Effective English Language Teaching Techniques - Indriyani, Zahra Syavira; Rakhmawati; Fithrijah, Siti Salisa (ICONELT, 2024)
Optimizing students’ learning potential is crucial in teaching English, as effective methods enhance comprehension and learning capacity. This study examines instructional techniques, focusing on project-based learning, cooperative learning, picture-based learning, and practice and repetition. Collaborative learning fosters a friendly environment for exchanging ideas and advancing language proficiency. Visual learners benefit from picture-based learning, which reinforces vocabulary and concepts. Project-based learning promotes collaboration, communication, and practical language application. Repeated practice helps internalize vocabulary, grammar, and listening abilities, boosting confidence in speaking English. The study employed qualitative methodologies, including questionnaires, teacher interviews, and classroom observations. Results showed that repeated practice and collaborative learning were most effective in overcoming learning difficulties, while picture and project-based learning contributed to engagement and understanding. Adaptable teaching strategies are needed to accommodate different learning styles and encourage active participation in English language learning.